Assessing the Effect of Surgical Procedure on Radiotherapy Dose to Lung in Breast Carcinomas - Nadeem, Muhammad Sohaib; Ali, Usman; Alvi, Zeeshan Ahmed (Pakistan Armed Forces Medical Journal, 2026)
Objective: To investigate the effect of surgical procedure, mastectomy versus breast conservation surgery (BCS) on radiotherapy dose to the lung, in patients of breast cancer treated with adjuvant radiotherapy (RT).   Study Design: Retrospective longitudinal study.Place and Duration of Study: Combined Military Hospital Rawalpindi, Pakistan over a period of 8 months, on patients treated between Jan 2023 - Aug 2023.Methodology: A total of 103 female breast cancer patients receiving an equivalent of 50 Gray in 25 fractions or more (upto 16 gray in 8 fractions or equivalent) of adjuvant radiotherapy to breast after breast conservation surgery (BCS) or chest wall (after mastectomy) were studied. All received field in field intensity modulated radiotherapy (IMRT) with tangential beams. Their lung doses were estimated by measuring the central lung distance (CLD), as a surrogate to volumetric lung dose. Data was analyzed by SPSS version 22. Pearson correlation was checked. Mean CLD between the two surgical groups was compared.Results: Of total 103 patients, 72(69.9%) had modified radical mastectomy (MRM) and 31(30.1%) had breast conservation surgery (BCS). Surgical procedure mastectomy versus breast conservation surgery has a significant correlation with CLD (r= -0.27, p-value 0.005). Mean CLD after MRM was 2.71±0.63 cm and after BCS was 2.34±0.49 cm with a statistically significant difference (p-value - 0.005).Conclusion: Breast conservation surgery (BCS) not only spares the organ but also reduces the radiation toxicity due to lower effective ....